Emergency medical surgical treatment in 18 to 26 week s pregnant women with cervical incompetence - Farro, Andrés (2015)
OBJETIVE: To determine whether the combined treatment of decompression of the amniotic sac and prolonged pregnancies with cerclage cervical incompetence (CI), complicated by dilation of the cervix and protrusion of the amniotic sac in pregnant women aged 18-26 weeks. DESIGN: Retrospective observational study. PLACE: Edgardo Rebagliati Martins National Hospital, EsSalud, Lima, Peru, University Hospital. MATERIALS AND METHODS: Fifteen pregnant women in 18-26 weeks IC, protrusion of the amniotic sac, served between the years 1998-2002. Banding technique used in the first 7 cases was the first step of the technique Wurm and in the last 8 cases Rebagliati use the technique, which is described below. RESULTS: Cervical cerclage was performed in 15 cases. Decompressive amniocentesis previously made in 12 cases with 'hourglass bag. "He managed to prolong pregnancies between 0 and 20 weeks (mean 9.53 weeks, 6.42). One of the cases was treated multiple pregnancy (triplets .) Of the 17 products of conception, 2 were deaths;. of the 15 who were born alive (88%), 1 died of immaturity and 1, congenital malformations (triplet) and 13 survived (76.5%) Type calving in the treated patients was 47% vaginal and cesarean in 53%, with mean gestational age of 33.77 weeks (range 22-39 weeks), birth weight with an average of 2012 g of 900 (range 550 to . 3800g) CONCLUSIONS: cerclage, prior amnioreduction when the protrusion of the amniotic sac is severe, it appears to be beneficial in pregnancy advanced gestational age (18-26 weeks) with HF presented dilation of the cervix and protrusion of the amniotic sac.